Key recommendations to strengthen public-private partnership for adolescent health in resource constrained settings: Formative qualitative inquiry in Mongolia, Myanmar and the Philippines. - Peter S Azzopardi; Julie Hennegan; Shirley Mark Prabhu; Bolorchimeg Dagva; Mx Mar Balibago; Pa Pa Win Htin; Zay Yar Swe; Elissa C Kennedy (Elsevier, 2021)
Background: Public health services can be inaccessible for adolescents. The private sector provides many services, but often in parallel to the public sector. This study aimed to understand current private sector engagement in adolescent health service delivery and develop recommendations to strengthen partnerships. Methods: The study focussed on Mongolia, Myanmar and the Philippines. An initial participatory workshop in each country was followed by semi-structured key-informant interviews (32 in total) with public and private sector actors and adolescents to explore: perceptions of the public and private sectors, strengths and challenges, existing models of partnership, and insights for successful public-private partnership (PPP). Interview transcripts were analysed thematically, with findings and recommendations verified through a second workshop in Mongolia and the Philippines. Findings: The private sector already plays a significant role in adolescent health care, and stakeholders reported a genuine willingness for partnership. Strengthened PPP was identified as necessary to improve service accessibility and quality for adolescents, unburden the public sector and introduce new technologies, with advantages for the private sector including improved access to training and resources, and an enhanced public image. Recommendations for strengthened PPP included the need to establish the foundations for partnership, clearly define roles and co-ordinate stakeholders, ensure capacity and sustainability, and monitor and evaluate efforts. Interpretation: This is the first comprehensive study of public-private partnership for adolescent health in the Asia Pacific region. It identifies stakeholders are willing for stronger partnerships and the benefits this partnership will bring. We define eight key recommendations to enable this partnership across sectors.